The use of video-based reflection to facilitate pre-service English teachers’ self-reflection - Indriretno Setyaningrahayu*; Pramusita Raring Widhi; Elisabet Titik Murtisari (Universitas Katolik Indonesia Atma Jaya, 2019)
As self-reflection is crucial for improving the professional identity of pre-service teachers, it is paramount to discover ways that may assist them to reflect more effectively. This study investigates how self-reflection may be enhanced by the use of video recording as compared to that which is facilitated only by students’ memories. Employing a descriptive qualitative analysis method, the research uses reflection journals and interviews from pre-service English teachers of two available microteaching classes of an English language education program in an Indonesian private university in Central Java. While the students in one class used video recording to help them reflect, those in the other class relied on memory. The findings showed that the reflections supported by video recording were more specific and more analytical, focusing more attention on management-related issues of the teaching. Those from the memory-based group, on the other hand, tended to be general and descriptive with more accounts on personal feelings.